Applications of RBI on leakage risk assessment of direct coal liquefaction process. (January 2017) - Dou, Zhan; Jiang, Jun-Cheng; Wang, Zhi-Rong; Pan, Xu-Hai; Shu, Chi-Min; Liu, Long-Fei
Abstract: Direct coal liquefaction process is the core of coal-to-liquids manufacturing. Due to the strict operating conditions and quantities of hazardous materials involving in the process, conceivable occurrence of leaking may lead to devastating accidents. In this paper, the risk-based inspection (RBI) technique is introduced to be applied in the leakage risk assessment of direct coal liquefaction process. According to the on-site investigation, four leakages rooted in abrasion, untightened seals, fatigue damage and cracks are determined. The hazardous materials potentially participating in the distinctive leakages consist of dry gas, hydrogen, hydrogen sulfide, sulfur, pulverized coal and liquefied light and heavy oil. Concerning the different occurrence probabilities and consequences of leakage, risk assessment and classification have been performed at all critical locations along process of direct coal liquefaction. Therewith, the corresponding scenarios and outcomes of leakage are determined, and accordingly detecting scheme and methods are proposed. The implementation of leakage risk assessment reinforces the inherently safer design of direct coal liquefaction process. Graphical abstract: Highlights: It is first time to introduce RBI technique to estimate the leakage risk of direct coal liquefaction process. In the direct coal liquefaction process, four types of leakage are determined. The probability and consequence categories for leakage risk assessment are ascertained through three ways. The leakage risk of 885 pipes and 124 vessels are obtained and confirmed as well as the global inspection plan.